Prevalence of Depression and its determinants among undergraduate Medical college students in Salem, Tamil Nadu - Ramu, Suruthi; Dhanasekar, G; Babu, Gautam; Kumar, Mohan; Shanmugam, Jeevithan (Indian Journal of Community Health, 2023)
Background: Stress is an essential determinant of depression, leading to a greater prevalence of depression among medical students than the general population; a vulnerable subgroup. The objective of the present study was to determine the prevalence of depression and its associated factors among undergraduate medical students. Methods: This was an analytical cross-sectional study conducted among medical college students in Salem, Tamil Nadu between October 2021, and December 2022. Beck’s Depression Inventory (BDI) was used. Results: The prevalence of depression among undergraduate medial students was 27.0%; 10.2% had mild depression, 5.4% had borderline clinical depression, 8.5% had moderate depression, 2.4% had severe depression, and 0.5% had extreme depression. Multivariate logistic regression analysis showed that presence of separated or divorced or single parent, being in Phase II, without satisfactory academic performance, presence of active or chief complaints, conflicts in the family, and recent failures were independent predictors of depression among undergraduate medical students (p<0.05). Conclusion: It is crucial that medical schools prioritize the mental health of their students and provide appropriate resources and support.